HUBUNGAN PARTISIPASI KELAS IBU HAMIL DENGAN KEJADIAN KETUBAN PECAH DINI DI PUSKESMAS JEBED KABUPATEN PEMALANG - Resty Himma Muliani; Sa’adah Handayani (Jurnal Ilmiah Kebidanan Imelda, 2025)
Introduction: Beyond reducing the risk of infection, no prophylactic strategies are currently available, and the cause of premature rupture of membranes remains unknown. Prenatal seminars can be used to educate and support pregnant women on how to manage premature rupture of membranes, among other initiatives. Objective: The aim of this study was to determine how the prevalence of premature rupture of membranes at the Mampu Bersalin Jebed Community Health Center in Pemalang Regency is associated with enrollment in prenatal classes. Methods: This study used a cross-sectional design and quantitative methodology. Using a purposive sampling approach, the sample size was 84 respondents, 42 of whom were mothers who experienced premature rupture of membranes and 42 of whom did not. The Spearman Rank correlation test was used to analyze secondary data from the community health center's medical records at a 5% significance level. Results: 24 respondents, or 28.6% of mothers with BPD, were mostly actively involved in prenatal classes, while 26 respondents, or 31% of mothers without BPD, participated primarily passively. With a p-value of 0.082, Spearman's Rank correlation test analysis did not reveal an association between attending prenatal classes and the risk of premature rupture of membranes. Conclusion: Based on the research results, it shows that there is no relationship between participation in pregnancy classes and the incidence of KPD with a p value of 0.082.